2009
DOI: 10.1080/17518420902991719
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality in paediatric rehabilitation: A review

Abstract: VR may be an effective treatment method for specific disorders, although the generalizability of this literature is hindered by several methodological limitations, such as small samples and the absence of appropriate control participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(75 citation statements)
references
References 48 publications
1
73
0
1
Order By: Relevance
“…stroke, traumatic brain injury, spinal cord injury, cerebral palsy, multiple sclerosis, etc.) (Deutsch & McCoy, 2017; Howard, 2017; Klamroth-Marganska et al, 2014; Lange et al, 2012; Merians et al, 2010), and for the assessment and rehabilitation of attention, memory, spatial skills, and other cognitive functions in both clinical and unimpaired populations (Bogdanova, Yee, Ho, & Cicerone, 2016; Matheis et al, 2007; Parsons, Rizzo, Rogers, & York, 2009; Pugnetti et al, 1995; Rizzo, 1994; Rizzo et al, 2006; Valladares-Rodriguez et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…stroke, traumatic brain injury, spinal cord injury, cerebral palsy, multiple sclerosis, etc.) (Deutsch & McCoy, 2017; Howard, 2017; Klamroth-Marganska et al, 2014; Lange et al, 2012; Merians et al, 2010), and for the assessment and rehabilitation of attention, memory, spatial skills, and other cognitive functions in both clinical and unimpaired populations (Bogdanova, Yee, Ho, & Cicerone, 2016; Matheis et al, 2007; Parsons, Rizzo, Rogers, & York, 2009; Pugnetti et al, 1995; Rizzo, 1994; Rizzo et al, 2006; Valladares-Rodriguez et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Sensory integration approach is one of the interventions that commonly and positively affect the rehabilitation of autistic children [16,17]. Virtual reality (VR) is recently used as a talented method in pediatric rehabilitation [18].…”
Section: Discussionmentioning
confidence: 99%
“…These studies were showed to increase of sensorimotor functions and motor proiciency by using VR in these disabilities [27,40].…”
Section: Studies On Vr In Pediatric Rehabilitationmentioning
confidence: 99%